1999
DOI: 10.1016/s0006-3495(99)76922-5
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Exciton Model for the Core Light-Harvesting Antenna of Rhodopseudomonas viridis

Abstract: In this work we explain the spectral heterogeneity of the absorption band (. Biochim. Biophys. Acta. 1229:373-380), as well as the spectral evolution of pump-probe spectra for membranes of Rhodopseudomonas (Rps.) viridis. We propose an exciton model for the LH1 antenna of Rps. viridis and assume that LH1 consists of 24-32 strongly coupled BChl b molecules that form a ring-like structure with a 12- or 16-fold symmetry. The orientations and pigment-pigment distances of the BChls were taken to be the same as for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 51 publications
4
90
0
Order By: Relevance
“…This means that we are not able to estimate the delocalization length from the shape of the pump-probe spectra only. On the other hand, we have also calculated the amplitude of the bleaching peak of the pump-probe spectra normalized to the bleaching of the BChl monomer 17 and we found that this relative bleaching value was varying from 5.4 to 11.2 in close correlation with the N eff value. So, the amplitude of the difference absorption contains information that can be used for a more precise estimation of the delocalization parameters.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…This means that we are not able to estimate the delocalization length from the shape of the pump-probe spectra only. On the other hand, we have also calculated the amplitude of the bleaching peak of the pump-probe spectra normalized to the bleaching of the BChl monomer 17 and we found that this relative bleaching value was varying from 5.4 to 11.2 in close correlation with the N eff value. So, the amplitude of the difference absorption contains information that can be used for a more precise estimation of the delocalization parameters.…”
Section: Introductionmentioning
confidence: 84%
“…If we switch on the disorder, these values will be even smaller. Thus, modeling of the LH1 and LH2 antennas with the presence of static disorder gave the values N eff ) 5-11 6,8,17,21,30 and N coh ) 4-6 17,21,25 at room temperature. In all these models the exciton-phonon coupling was supposed to be weak.…”
Section: Introductionmentioning
confidence: 97%
“…All RP- † A similar analysis to determine the exciton delocalization length in bacterial lightharvesting antenna systems was applied in ref. 37. HPLC-purified oligodeoxynucleotides were purchased from Midland Certified Reagent Company (Midland, TX).…”
Section: Methodsmentioning
confidence: 99%
“…Excitons can extend over multiple chromophores [30][31][32] and can have a profound impact on the electronic structure and hence optical properties of the system as well as on energy transfer dynamics. Clear examples of excitons have been discovered in ensemble-averaged linear and nonlinear spectroscopy experiments [31][32][33][34][35][36][37][38][39] as well as single-molecule spectroscopy of LH2 from purple photosynthetic bacteria [40,41]. The latter have provided strong evidence for delocalized excited states immediately after the excitation of a single LH2.…”
Section: Energy Transfer and The Question Of Coherencementioning
confidence: 99%